2008
DOI: 10.1002/cbic.200700559
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Tobacco Mosaic Virus with “Click” Chemistry

Abstract: Click conjugation of tobacco mosaic virus: As a prototype of “click” chemistry, the CuI catalyzed azide‐alkyne cycloaddition reaction in combination with diazonium‐coupling proved to be an efficient, versatile, and benign method to conjugate a wide range of compounds to phenolic groups of protein tyrosines. In particular, plant virus tobacco mosaic virus was chosen as a multivalent protein scaffold to demonstrate this bioconjugation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
214
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 197 publications
(220 citation statements)
references
References 59 publications
4
214
0
1
Order By: Relevance
“…This reaction has been extensively used in materials development [6][7][8][9], polymer synthesis [10,11], dendrimer synthesis [12][13][14][15][16] and drug discovery [17][18][19]. CuAAC reaction serves as a great tool for bioconjugation applications [20][21][22][23][24][25][26][27][28][29], mainly due to (i) facile synthesis and easy incorporation of alkyne and azide moieties into biomolecular frameworks, (ii) compatibility to other functionalities yielding highly specific products, (iii) compatibility to water which is crucial for biomolecular systems, (iv) mild reaction conditions which will help maintaining the properties of biomolecules, and (v) stability of the resulting triazole ring to the hydrolytic cleavage, oxidation and reduction [2,3,9].…”
Section: Introductionmentioning
confidence: 99%
“…This reaction has been extensively used in materials development [6][7][8][9], polymer synthesis [10,11], dendrimer synthesis [12][13][14][15][16] and drug discovery [17][18][19]. CuAAC reaction serves as a great tool for bioconjugation applications [20][21][22][23][24][25][26][27][28][29], mainly due to (i) facile synthesis and easy incorporation of alkyne and azide moieties into biomolecular frameworks, (ii) compatibility to other functionalities yielding highly specific products, (iii) compatibility to water which is crucial for biomolecular systems, (iv) mild reaction conditions which will help maintaining the properties of biomolecules, and (v) stability of the resulting triazole ring to the hydrolytic cleavage, oxidation and reduction [2,3,9].…”
Section: Introductionmentioning
confidence: 99%
“…A Cu(I)-catalyzed azide-alkyne 1,3-dipolar cycloaddition (CuAAC) reaction was then performed to conjugate RGD-azide to the alkyne groups. 21 The CuAAC reaction was very efficient, and more than 90% of alk-M13 was transferred to RGD-modified M13 (RGD-M13).…”
mentioning
confidence: 99%
“…tyrosine residues of TMV coat proteins to insert a terminal alkyne. 1,27,44 This was achieved using a diazonium salt generated in situ from 3-ethynylaniline then mixed with TMV to form the corresponding alkyne labeled TMV (Alkyne-TMV). MALDI-TOF MS analysis indicated that >95% of the capsid monomers were converted to the alkyne derivatives as seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…22 TMV has been employed as a building block or template to produce materials with applications in light harvesting, electronics, energy storage, and cell culturing. 3,[23][24][25][26][27] On the other hand, conducting polymers have found broad applications in electronics, imaging and sensing. [28][29][30] In particular, polyaniline (PANI) has received considerable attention due to its environmental stability, ease of synthesis and its well known physical properties.…”
Section: Introductionmentioning
confidence: 99%